METHODOLOGICAL ASPECTS OF USING THE GOOGLE TRANSLATE APPLICATION TO FOREIGN LANGUAGE LESSONS - Tatiana VEVERIȚA (Acta et Commentationes, Sciences of Education, 2019)
This article analyzes the role of Google Translate in studying foreign languages. The mainideas of the article relate the importance of information technologies in the development of foreignlanguage learning skills and how these can become pedagogical tools that help to increase the level ofunderstanding of a foreign language